To See and to Tell: Lessing’s Criticism of Ageism in The Diary of a Good Neighbor - LI , Huifang; LIU , Chunrui (Journal of Social Science Studies, 2021)
The Diary of a Good Neighbor is one of a series of works concerning age problems in the contemporary western society written by the Nobel laureate Doris Lessing. Through the record of the last days of Maudie Fowler, a ninety-two-year-old lower-class woman by a middle-aged professional Jane Somers, Lessing questions the modern social care system and criticizes the hidden social prejudice against the elderly. Lessing observes the defect of the modern social care institutions in oppressing individual choice and excluding aged people, and points out the professional service they provide cannot really comfort the aged individuals, which constructs a dilemma for both the institutions and the aged group. Different from the ageist neglect of the aged group, Lessing gives a detailed exhibition of both Maudie’s daily life and her inner world, which builds a personal connection between the old and the young and draws this isolated group close to the public. Lessing also explores the taboo topic of old age, sickness and death and gives a full display of Maudie’s tenacious wrestling with death, which shows the sublime of human life and challenges the ageist view of the co-decaying of spirit and body.